PEMBERIAN TUGAS MEMBUAT PETA KONSEP (CONCEPT MAP) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA MAN 1 BENGKALIS - Annisa, Wilda Chaira; Copriady, Jimmi; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Has made the gived task to make concept map on the topic of colloid in class XI sains MAN 1 Bengkalis. This research aims to improve student achievement. The research is a kind of experiment research with pretest-posttest design. The population were all of the students of XI sains MAN 1 Bengkalis. The samples of this research were the students of class XI sains3 as the experimental class and students of class XI sains2 as the control class. Experimental class is a class that is gived task to make Concept Map while the control class was not. Data analysis technique used is the t-test with dk is 59 and α is 0,05.before t-test has made,the sampels had normal distribution and homogeneus. Based on data analysis of data obtained tcount> ttable is 2,42>1.67, means that the gived task to make Concept Map can improve student learning achievement on the topic of colloid in class IX Sains MAN 1 Bengkalis. The category improvement of student achievement at experiment class was high category with N-gain normalized is 0,75. Meanwhile, the category improvement of student achievement in control class was medium category with N-gain normalized is 0,66.Keywords : Achievement, Concept Map, Colloid